2022
DOI: 10.1038/s41467-022-28352-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of vibronic coupling in a 4f molecular magnet with FIRMS

Abstract: Vibronic coupling, the interaction between molecular vibrations and electronic states, is a fundamental effect that profoundly affects chemical processes. In the case of molecular magnetic materials, vibronic, or spin-phonon, coupling leads to magnetic relaxation, which equates to loss of magnetic memory and loss of phase coherence in molecular magnets and qubits, respectively. The study of vibronic coupling is challenging, and most experimental evidence is indirect. Here we employ far-infrared magnetospectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 55 publications
3
55
0
Order By: Relevance
“…We have shown herein that long phase memory times can be achieved in purely f-electron systems essentially devoid of orbital angular momentum since local fluctuations of the LF cannot couple via magnetoelastic coupling terms to the wave functions of the electronic system. These results are in agreement with previous studies on d- or f-shell molecular systems where isotropic states, thus devoid of orbital angular momentum, have been probed. ,, Furthermore, they are also in agreement with recent experimental and theoretical studies in which we demonstrated the importance of the magnetoelastic coupling and the role of the trigonal symmetry to the dynamic magnetic properties of the isostructural (displaying thus the same phonon spectrum) Yb­(trensal) complex . In addition, in previous coherent dynamics studies of Yb­(trensal), we have shown that the ground term displays a phase memory time of a few hundred nanoseconds for Yb 0.07 Lu 0.93 (trensal) at X-band, which gets T 1 limited and of the order of 0.1 μs at around 20 K. Preliminary measurements on single crystals of Yb 0.01 Lu 0.99 (trensal) at 240 GHz (Figure S14) show similar T m characteristics as those previously determined for Yb­(III) at X-band .…”
Section: Resultssupporting
confidence: 93%
“…We have shown herein that long phase memory times can be achieved in purely f-electron systems essentially devoid of orbital angular momentum since local fluctuations of the LF cannot couple via magnetoelastic coupling terms to the wave functions of the electronic system. These results are in agreement with previous studies on d- or f-shell molecular systems where isotropic states, thus devoid of orbital angular momentum, have been probed. ,, Furthermore, they are also in agreement with recent experimental and theoretical studies in which we demonstrated the importance of the magnetoelastic coupling and the role of the trigonal symmetry to the dynamic magnetic properties of the isostructural (displaying thus the same phonon spectrum) Yb­(trensal) complex . In addition, in previous coherent dynamics studies of Yb­(trensal), we have shown that the ground term displays a phase memory time of a few hundred nanoseconds for Yb 0.07 Lu 0.93 (trensal) at X-band, which gets T 1 limited and of the order of 0.1 μs at around 20 K. Preliminary measurements on single crystals of Yb 0.01 Lu 0.99 (trensal) at 240 GHz (Figure S14) show similar T m characteristics as those previously determined for Yb­(III) at X-band .…”
Section: Resultssupporting
confidence: 93%
“…Fitting results suggest that spin-lattice interaction dominates in the magnetization reversal process, which might correlate with the Raman signal observed in the LF region with the vibrational energy of 60 cm -1 or lower, suggesting the presence of phonon required to help the spin relaxation to happen through the Raman mechanism. [17] The obtained Orbach energy barrier for Dy 0.02 Y 0.98 Au is 90.83 K (63.1 cm -1 ) following Equation (E3), corroborating the energy gap between the m J states as predicted through ab initio calculation and underestimating by 63 cm -1 calculated with high-resolution emission spectra (Figure S23 and Table S15, Supporting Information). The ground state composition for Dy(III) ions computed by replacing neighboring Dy(III) ions with Y(III) ions reveals that it has an anisotropic magnetic easy axis (g z = 18.56); however accompanied by nonnegligible transversal components hampering the zero-dc-field slow magnetic relaxation (Figure S33, Table S15, Supporting Information).…”
Section: Magnetic Propertiessupporting
confidence: 76%
“…For such opto-magnetic lanthanide complexes, studying the vibrational signature in the LF region for Raman active modes through LF Raman spectroscopy can enhance our understanding of the dependence of physical properties (magnetic, optical) on structural changes. [17] Raman spectroscopy in the LF region has been used to detect various bonds of Au atoms in gold clusters, vibrational modes of pharmaceutical crystals, and phonons of graphene. [18] In this regard, Raman spectroscopy applied to a temperature sensor in the LF region (especially below 1 THz) has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetization barrier is deduced from the spin Hamiltonian. Supposing that the relaxation follow an Orbach relaxation scheme, it corresponds to the experimental value [76,77,78,79]. It is related to the anisotropy of the coupling, but is not affected by the anisotropy of the central g-tensor.…”
Section: Discussionmentioning
confidence: 99%